Ionic crosslinking type composite cellulose, diaphragm, preparation method and application

Through the design of the ion crosslinked composite cellulose separator, the problems of low lithium storage capacity of phosphorus negative electrodes and polyphosphine shuttle in lithium-ion batteries are solved, and the battery ratio and circulation performance are improved, while maintaining the thin and light diaphragm.

CN119591729APending Publication Date: 2025-03-11UNIV OF JINAN +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510013893.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the reversible lithium storage capacity of the phosphorus negative electrode is lower than the theoretical value, and commercial diaphragms cannot effectively block the shuttle of polyphosphides, limiting the battery's magnification and cycling performance.

Method used

Ion-crosslinked composite cellulose is used as the separator material, and cellulose is treated by aldehyde radicalization and sulfonation modification, and crosslinked with multivalent metal hydroxide nanoparticles to form a separator with a multi-scale structure and abundant ion-regulating sites.

Benefits of technology

The diaphragm can selectively prevent polyphosphorus anions from shuttleing across the diaphragm, improve the magnification and cycling performance of the lithium-ion battery, while keeping the diaphragm thin and avoiding the energy density reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591729A_ABST
    Figure CN119591729A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to ionic crosslinking type composite cellulose, a diaphragm, a preparation method and application, and the preparation method comprises the following steps: dispersing cellulose in water to obtain a cellulose suspension; adding sodium periodate into the cellulose suspension, and treating under a dark condition to obtain aldehyde cellulose; carrying out mixing treatment on the aldehyde cellulose and a sodium pyrosulfite aqueous solution to obtain a sulfonated modified cellulose suspension; after the sulfonated modified cellulose suspension and metal salt are mixed, sodium hydroxide is added for mixing treatment, and ionic crosslinking type composite cellulose is obtained; according to the present invention, the multi-phosphorus anion can be selectively prevented from shuttling across the diaphragm, the rate and the cycle performance of the lithium ion battery can be improved, and the weight and the thickness of the diaphragm are slightly increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and more specifically, to an ion-crosslinked composite cellulose, a separator, a preparation method and an application. Background Art

[0002] The information disclosed in this background section is intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Phosphorus has a high theoretical specific capacity (2596 mAh g -1 / 6075 mAh cm -3 ) and a moderate and safe lithium insertion potential (0.7 V vs. Li + / Li), is an ideal negative electrode material for fast-charging lithium-ion batteries with broad application prospects. However, due to the transmembrane shuttling effect of the intermediate product polyphosphide, the reversible lithium storage capacity of the phosphorus negative electrode is still far lower than its theoretical value, which seriously restricts the further development and practical application of phosphorus negative electrode-based lithium-ion batteries. More importantly, the currently commercially available diaphragms such as polyethylene and polypropylene cannot effectively block the shuttling of polyphosphides. Therefore, there is an urgent need to develop new diaphragm materials to improve the electrochemical lithium storage performance of phosphorus negative electrodes. In the context of "carbon neutrality", using natural biomass as a diaphragm material and utilizing its structural characteristics to solve the transmembrane shuttling problem of polyphosphides has important research significance and social value.

[0004] Studies have shown that the diaphragm modified with functional coating can effectively confine polyphosphides to the working electrode side through physical or chemical adsorption. The modified diaphragm is prepared by coating carbon nanotubes on the surface of commercial Celgard diaphragm, and the polyphosphides can be captured and stabilized by physical adsorption between the carbon nanotube modified layer and the polyphosphides. Compared with carbon nanotubes, materials such as lithium fluoride and MXene have stronger interactions with polyphosphides, and can adsorb polyphosphides by forming chemical bonds or Lewis acid-base reactions, preventing them from shuttling to the counter electrode side. However, although constructing a functional coating can enhance the adsorption of polyphosphides by the diaphragm, it will inevitably increase the weight and thickness of the diaphragm, resulting in a decrease in the energy density of the battery. In addition, the coating material will cover or fill the pores of the diaphragm, which will not only block the shuttling of polyphosphides, but also hinder the transmission of lithium ions. Summary of the invention

[0005] The present application is provided to solve the above-mentioned defects existing in the prior art. An ion-crosslinked composite cellulose, a separator, a preparation method and an application are needed, which can selectively prevent polyphosphorus anions from shuttling across the separator and can improve the rate and cycle performance of lithium-ion batteries, and the weight and thickness of the separator are increased very little.

[0006] In a first aspect of the present application, a method for preparing an ionically cross-linked composite cellulose is provided, the method comprising: dispersing cellulose in water to obtain a cellulose suspension; adding sodium periodate to the cellulose suspension and treating it in the dark to obtain formaldehyded cellulose; mixing the formaldehyded cellulose with an aqueous solution of sodium pyrosulfite to obtain a sulfonated modified cellulose suspension; mixing the sulfonated modified cellulose suspension with a metal salt, and then adding sodium hydroxide for mixing to obtain an ionically cross-linked composite cellulose.

[0007] In a second aspect of the present application, there is provided an ionically cross-linked composite cellulose obtained by the preparation method described in any embodiment of the present application.

[0008] The third aspect of the present application provides a method for preparing an ionically cross-linked composite cellulose membrane, the preparation method comprising: adding sodium hydroxide to the preparation method of the ionically cross-linked composite cellulose described in any embodiment of the present application for mixing and then filtering to obtain a wet film; soaking the wet film in anhydrous ethanol; and drying the soaked wet film under clamping to obtain an ionically cross-linked composite cellulose membrane.

[0009] The fourth aspect of the present application provides an ion-crosslinked composite cellulose membrane obtained by the preparation method described in any embodiment of the present application.

[0010] The fifth aspect of the present application provides a method for preparing the ion-crosslinked composite fiber described in any embodiment of the present application, the ion-crosslinked composite cellulose described in any embodiment of the present application, a method for preparing the ion-crosslinked composite cellulose membrane described in any embodiment of the present application, and / or the use of the ion-crosslinked composite cellulose membrane described in any embodiment of the present application in a lithium-ion battery.

[0011] The ion-crosslinked composite cellulose, diaphragm, preparation method and application provided in each embodiment of the present application, cellulose is a green chemical product extracted from natural organisms, has the advantages of being cheap, easily available and biodegradable, so the ion-crosslinked composite cellulose diaphragm obtained in the present application has broad application prospects; the ion-crosslinked composite cellulose is obtained through the preparation process, and a structure cross-linked by sulfonic acid groups and multivalent metal hydroxides is formed on the ion-crosslinked composite cellulose, so that the ion-crosslinked composite cellulose has a multi-scale structure and abundant ion regulation sites, which is helpful to improve the rate and cycle performance of phosphorus negative electrode-based lithium-ion batteries, break through the limitation of traditional functional coatings that use binders to reduce energy density, and can also avoid the reduction of battery energy density due to the heavy weight and thickness of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.

[0013] Figure 1 The scanning electron microscope image of the ion-crosslinked composite cellulose separator obtained according to Example 1 of the present application is shown; Figure 2 The infrared spectrum of the ion-crosslinked composite cellulose separator obtained according to Example 1 of the present application is shown; Figure 3 The scanning electron microscope image of the sulfonated modified cellulose diaphragm obtained according to Comparative Example 1 of the present application is shown; Figure 4 The infrared spectrum of the sulfonated modified cellulose membrane obtained according to Comparative Example 1 of the present application is shown; Figure 5 The cycle performance diagram of a phosphorus negative electrode-based lithium ion battery assembled using the ion-crosslinked composite cellulose separator obtained in Example 1, the sulfonated modified cellulose separator obtained in Comparative Example 1, and the commercial separator Celgard 2400 is shown according to the present application; Figure 6 The effect diagram of inhibiting the transmembrane shuttling of polyphosphides by using the ion-crosslinked composite cellulose membrane obtained in Example 1 and the commercial membrane Celgard 2400 according to the present application is shown; Figure 7 The cycle performance diagram of the phosphorus negative electrode-based lithium ion battery assembled with the ion-crosslinked composite cellulose separator obtained in Example 2 according to the present application is shown. DETAILED DESCRIPTION

[0014] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.

[0015] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.

[0016] According to an embodiment of the present application, a method for preparing an ionically cross-linked composite cellulose is provided, the method comprising: dispersing cellulose in water to obtain a cellulose suspension; adding sodium periodate (NaIO4) to the cellulose suspension, and treating it under dark conditions to obtain formaldehyded cellulose; mixing the formaldehyded cellulose with an aqueous solution of sodium pyrosulfite (Na2S2O5) to obtain a sulfonated modified cellulose suspension; mixing the sulfonated modified cellulose suspension with a metal salt, and then adding sodium hydroxide for mixing to obtain an ionically cross-linked composite cellulose.

[0017] The cellulose suspension is first mixed with sodium periodate, which selectively oxidizes cellulose and oxidizes the hydroxyl groups at the C2 and C3 positions of cellulose into aldehyde groups to generate dialdehyde cellulose, also known as formaldehyde cellulose. Sodium pyrosulfite is a sulfonating agent that replaces the aldehyde groups on formaldehyde cellulose with sulfonic acid groups to generate sulfonated cellulose. After adding metal salts, sodium ions are exchanged for other metal ions through ion exchange. The negatively charged sulfonic acid groups will combine with the added multivalent metal cations to form a cross-linked structure. Finally, sodium hydroxide is added to convert the metal ions into metal hydroxide nanoparticles.

[0018] The obtained ion-crosslinked composite cellulose forms a multi-scale structure centered on polyvalent metal ions, and produces dense and evenly distributed ion regulation sites at the molecular level; the sulfonic acid groups can selectively prevent the multi-phosphorus anions from shuttling across the membrane through electrostatic repulsion, while providing lithium ion migration sites to guide their rapid transmission; the multi-valent metal ions can fix the multi-phosphorus anions on the phosphorus negative electrode side of the membrane through Lewis acid-base effects, and form a multi-phosphorus anion barrier layer in situ through charge enrichment, thereby achieving the synergistic inhibition of the sulfonic acid groups and metal ions on the shuttling of multi-phosphorus compounds across the membrane.

[0019] The preparation method of the present application organically integrates chemical modification, ion exchange, vacuum filtration, solvent replacement and other processes to prepare an ion-crosslinked composite cellulose membrane. The method has the advantages of simple operation, easy acquisition of raw materials, and degradable products.

[0020] In some embodiments, the cellulose suspension has a cellulose mass concentration of 0.1-2.0%.

[0021] In some embodiments, after sodium periodate is added to the cellulose suspension, the concentration of sodium periodate in the cellulose suspension is 0.003-0.006 mol / L.

[0022] In some embodiments, the treatment time under dark conditions is 60-80 hours and the temperature is 20-30°C.

[0023] In some embodiments, the concentration of the sodium metabisulfite aqueous solution is 0.03-0.08 mol / L; the initially modified cellulose is mixed with the sodium metabisulfite aqueous solution for treatment, including: a treatment time of 40-50 hours and a treatment temperature of 20-30°C.

[0024] In some embodiments, the sulfonated modified cellulose suspension and the metal salt are mixed, including mixing a metal salt aqueous solution with the sulfonated modified cellulose suspension, wherein the concentration of the metal salt aqueous solution is 0.05-0.2 mol / L; the volume ratio of the metal salt aqueous solution to the sulfonated modified cellulose suspension is 1:(300-30). Preferably, the volume ratio of the metal salt aqueous solution to the sulfonated modified cellulose suspension is 1:(200-100). Further preferably, the volume ratio of the metal salt aqueous solution to the sulfonated modified cellulose suspension is 1:(160-140).

[0025] In some embodiments, the sulfonated modified cellulose suspension and the metal salt are mixed and treated for 5-15 minutes.

[0026] In some embodiments, adding sodium hydroxide for mixing treatment includes: adding sodium hydroxide aqueous solution, wherein the concentration of the sodium hydroxide aqueous solution is 0.05-0.2 mol / L; the volume ratio of the sodium hydroxide aqueous solution to the sulfonated modified cellulose suspension is 1:(100-10). Preferably, the volume ratio of the sodium hydroxide aqueous solution to the sulfonated modified cellulose suspension is 1:(60-40).

[0027] In some embodiments, the time for adding sodium hydroxide and mixing is 5-15 minutes.

[0028] In some embodiments, the cellulose is bacterial cellulose and / or plant-based cellulose, wherein the plant-based cellulose is cellulose extracted from cotton, straw, discarded bamboo chopsticks and / or wood waste.

[0029] In some embodiments, the metal salt is at least one of chloride, acetate, sulfate, and nitrate of iron, cobalt, nickel, copper, zinc, molybdenum, tungsten, indium, tin, bismuth, magnesium, aluminum, and calcium.

[0030] According to an embodiment of the present application, there is also provided an ion-crosslinked composite cellulose obtained by the preparation method described in any embodiment of the present application.

[0031] According to an embodiment of the present application, a method for preparing an ionically cross-linked composite cellulose membrane is also provided, and the preparation method comprises: in the method for preparing the ionically cross-linked composite cellulose described in any embodiment of the present application, sodium hydroxide is added for mixing treatment and then filtered to obtain a wet film; the wet film is soaked in anhydrous ethanol; the soaked wet film is dried under clamping to obtain the ionically cross-linked composite cellulose membrane.

[0032] The diaphragm is treated with ethanol immersion to obtain excellent porosity, and has very good electrolyte wettability and interface compatibility, which is beneficial to reducing battery impedance and rapid movement of ions under high current density conditions.

[0033] According to an embodiment of the present application, an ion-crosslinked composite cellulose separator obtained by the preparation method described in any embodiment of the present application is also provided. Compared with existing commercial separators, the ion-crosslinked composite cellulose separator can better inhibit the shuttling of polyphosphides across the separator, and can greatly improve the rate and cycle performance of phosphorus negative electrode-based lithium-ion batteries.

[0034] According to the embodiments of the present application, there is also provided a method for preparing the ion-crosslinked composite fiber described in any embodiment of the present application, the ion-crosslinked composite cellulose described in any embodiment of the present application, a method for preparing the ion-crosslinked composite cellulose membrane described in any embodiment of the present application, and / or the use of the ion-crosslinked composite cellulose membrane described in any embodiment of the present application in a lithium-ion battery.

[0035] Example 1 (1) dispersing bacterial cellulose in deionized water to obtain a cellulose suspension with a mass concentration of 0.287%; (2) Add 0.005 mol / L sodium periodate to the suspension obtained in (1), stir and react for 72 h in the dark at a temperature of 25°C, repeatedly centrifuge and wash the product until the supernatant becomes neutral, and collect the precipitate; (3) Ultrasonic dispersion of the precipitate obtained in (2) into a 0.05 mol / L sodium metabisulfite aqueous solution, stirring and reacting for 48 h at a reaction temperature of 25°C to obtain a stable suspension; (4) The suspension obtained in (3) was centrifuged and washed to obtain 50 mL of sulfonated modified cellulose suspension; (5) Add 0.34 mL of 0.1 mol / L AlCl3 aqueous solution to the suspension obtained in (4) and stir for 10 min; (6) Slowly drop 1.02 mL of 0.1 mol / L sodium hydroxide aqueous solution into the suspension obtained in (5) and stir for 10 min; (7) Wash and filter the suspension obtained in (6) to obtain a wet membrane, and soak it in anhydrous ethanol for 2 h; (8) The wet membrane obtained in (7) is sandwiched with a filter membrane and placed between two glass plates to keep it flat. After drying, an ion-crosslinked composite cellulose membrane is obtained.

[0036] Example 2 (1) dispersing bacterial cellulose in deionized water to obtain a cellulose suspension with a mass concentration of 0.287%; (2) Add 0.005 mol / L sodium periodate to the suspension obtained in (1), stir and react for 72 h in the dark at a temperature of 25°C, repeatedly centrifuge and wash the product until the supernatant becomes neutral, and collect the precipitate; (3) Ultrasonic dispersion of the precipitate obtained in (2) into a 0.05 mol / L sodium metabisulfite aqueous solution, stirring and reacting for 48 h at a reaction temperature of 25°C to obtain a stable suspension; (4) The suspension obtained in (3) was centrifuged and washed to obtain 50 mL of sulfonated modified cellulose suspension; (5) Add 0.71 mL of 0.1 mol / L AlCl3 aqueous solution to the suspension obtained in (4) and stir for 10 min; (6) Slowly drop 2.13 mL of 0.1 mol / L sodium hydroxide aqueous solution into the suspension obtained in (5) and stir for 10 min; (7) Wash and filter the suspension obtained in (6) to obtain a wet membrane, and soak it in anhydrous ethanol for 2 h; (8) The wet membrane obtained in (7) is sandwiched with a filter membrane and placed between two glass plates to keep it flat. After drying, an ion-crosslinked composite cellulose membrane is obtained.

[0037] Comparative Example 1 (1) dispersing bacterial cellulose in deionized water to obtain a cellulose suspension with a mass concentration of 0.287%; (2) Add 0.005 mol / L sodium periodate to the suspension obtained in (1), stir and react for 72 h in the dark at a temperature of 25°C, repeatedly centrifuge and wash the product until the supernatant becomes neutral, and collect the precipitate; (3) Ultrasonic dispersion of the precipitate obtained in (2) into a 0.05 mol / L sodium metabisulfite aqueous solution, stirring and reacting for 48 h at a reaction temperature of 25°C to obtain a stable suspension; (4) The suspension obtained in (3) was centrifuged, washed, and filtered to obtain a sulfonated modified cellulose wet membrane, which was then soaked in anhydrous ethanol for 2 h; (5) The wet membrane obtained in (4) is sandwiched with a layer of filter membrane and placed between two glass plates to keep it flat. After drying, a sulfonated modified cellulose membrane is obtained.

[0038] Assembly and testing of phosphorus negative electrode-based lithium ion battery: Red phosphorus (P) powder and multi-walled carbon nanotube (CNTs) powder were physically mixed in a mass ratio of 7:3 and sealed in a zirconia ball mill to control the ball-to-material ratio. Then, under an argon atmosphere, the mixture was ball milled at a speed of 400 rpm for 24 hours to obtain P-CNTs powder. Finally, P-CNTs powder, carbon black and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1 in N-methylpyrrolidone solvent to form a uniform slurry, which was coated on copper foil and vacuum dried to obtain a phosphorus negative electrode plate; lithium sheet was used as the counter electrode, and the ion-crosslinked composite cellulose diaphragm obtained in Example 1, the ion-crosslinked composite cellulose diaphragm obtained in Example 2, the sulfonated modified cellulose diaphragm obtained in Comparative Example 1 and the commercial diaphragm Celgard2400 were placed between the positive and negative electrodes to assemble a CR2032 lithium ion battery; a constant current charge and discharge test was performed using a CT4008 test device, with a voltage range of 0.01-3.0 V.

[0039] Figure 1 The scanning electron microscope image of the ion-crosslinked composite cellulose membrane obtained in Example 1. Compared with the sulfonated modified cellulose membrane, the fiber structure of the sulfonated modified cellulose was not destroyed during the in-situ loading process. The sample showed a fiber interlaced morphology. - and Al 3+ Due to the electrostatic attraction between ions, aluminum hydroxide nanoparticles are uniformly attached to the surface of sulfonated modified cellulose fibers.

[0040] Figure 2 This is the infrared spectrum of the ion-crosslinked composite cellulose membrane obtained in Example 1. 1643 and 1056 cm -1 The peak at 482 cm-1 can be attributed to the OH bending vibration of adsorbed water and the COC stretching vibration of the pyran ring, showing obvious cellulose characteristic peaks. -1 A new peak appeared at 1202 cm, which belongs to the stretching vibration of Al-O, confirming that the aluminum hydroxide nanoparticles have been successfully anchored on the sulfonated modified cellulose. -1 and 815 cm -1 The absorption peaks at 815 cm-1 and 816 cm-2 are attributed to the asymmetric S=O and symmetric COS vibrations in CO-SO3, respectively. -1 ) is decreased, which is due to the strong interaction between the sulfonic acid groups and aluminum hydroxide nanoparticles.

[0041] Figure 3 This is a scanning electron microscope image of the sulfonated modified cellulose membrane obtained in Comparative Example 1. The results show that the sulfonation modification process does not destroy the fiber structure of bacterial cellulose, and the sample exhibits a fiber interlaced morphology with a fiber diameter of about tens of nanometers.

[0042] Figure 4 The infrared spectrum of the sulfonated modified cellulose membrane obtained in Comparative Example 1 is shown in Figure 1. The results show that at 1240 cm -1 The peak at 1202 cm is due to the asymmetric S=O stretching vibration, while the peak at 1202 cm -1 The peaks at 613 and 1159 cm -1 A peak related to SO2 vibration appears at , indicating that the sulfonation modification is successful.

[0043] Figure 5 The cycle performance diagram of the phosphorus negative electrode based lithium ion battery assembled with the ion-crosslinked composite cellulose separator obtained in Example 1, the sulfonated modified cellulose separator obtained in Comparative Example 1 and the commercial separator Celgard2400, wherein SBC corresponds to the sulfonated modified cellulose separator obtained in Comparative Example 1, and ASBS corresponds to the ion-crosslinked composite cellulose separator obtained in Example 1 of the present application. The results show that the phosphorus negative electrode based lithium ion battery assembled with the ion-crosslinked composite cellulose separator obtained in Example 1 has a cycle performance of 1 A g -1 After 1000 cycles at the same current density, the remaining discharge capacity is 546 mAh g -1 , which are superior to the phosphorus negative electrode-based lithium ion batteries assembled using the sulfonated modified cellulose membrane obtained in Comparative Example 1 and the commercial membrane Celgard2400.

[0044] Figure 6 The figure shows the effect of using the ion-crosslinked composite cellulose membrane obtained in Example 1 and the commercial membrane Celgard2400 to inhibit the shuttling of polyphosphides across the membrane, where ASBS corresponds to the ion-crosslinked composite cellulose membrane obtained in Example 1 of the present application. The results show that the ion-crosslinked composite cellulose membrane obtained in Example 1 has a significantly better inhibitory effect on the shuttling of polyphosphides than the commercial membrane Celgard2400.

[0045] Figure 7 The cycle performance diagram of the phosphorus negative electrode based lithium ion battery assembled with the ion-crosslinked composite cellulose diaphragm obtained in Example 2. The results show that the phosphorus negative electrode based lithium ion battery assembled with the ion-crosslinked composite cellulose diaphragm obtained in Example 2 has a good cycling performance at 1 A g -1 After 1000 cycles at the same current density, the remaining discharge capacity is 430 mAh g -1 , which are superior to the phosphorus negative electrode-based lithium ion batteries assembled using the sulfonated modified cellulose membrane obtained in Comparative Example 1 and the commercial membrane Celgard2400.

[0046] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.

[0047] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.

[0048] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A method for preparing an ion-crosslinked composite cellulose, characterized in that: The preparation method comprises: dispersing cellulose in water to obtain a cellulose suspension; adding sodium periodate to the cellulose suspension and treating it in the dark to obtain formaldehyded cellulose; mixing the formaldehyded cellulose with an aqueous sodium pyrosulfite solution to obtain a sulfonated modified cellulose suspension; mixing the sulfonated modified cellulose suspension with a metal salt and then adding sodium hydroxide to obtain an ion-crosslinked composite cellulose.

2. The preparation method according to claim 1, characterized in that: The cellulose mass concentration of the cellulose suspension is 0.1-2.0%; After sodium periodate is added to the cellulose suspension, the concentration of sodium periodate in the cellulose suspension is 0.003-0.006 mol / L; The treatment time is 60-80 hours under dark conditions; the temperature is 20-30℃.

3. The preparation method according to claim 1, characterized in that: The concentration of the sodium metabisulfite aqueous solution is 0.03-0.08 mol / L; the initially modified cellulose is mixed with the sodium metabisulfite aqueous solution for treatment, including: a treatment time of 40-50 hours and a treatment temperature of 20-30°C.

4. The preparation method according to claim 1, characterized in that: The sulfonated modified cellulose suspension and the metal salt are mixed, comprising: mixing a metal salt aqueous solution with the sulfonated modified cellulose suspension, wherein the concentration of the metal salt aqueous solution is 0.05-0.2 mol / L; and the volume ratio of the metal salt aqueous solution to the sulfonated modified cellulose suspension is 1:(300-30). The mixing treatment time of the sulfonated modified cellulose suspension and the metal salt is 5-15 minutes.

5. The preparation method according to claim 1, characterized in that: The method comprises adding sodium hydroxide for mixing, wherein the sodium hydroxide aqueous solution has a concentration of 0.05-0.2 mol / L and the volume ratio of the sodium hydroxide aqueous solution to the sulfonated modified cellulose suspension is 1:(100-10). The time for adding sodium hydroxide and mixing treatment is 5-15 minutes.

6. The preparation method according to claim 1, characterized in that: The cellulose is bacterial cellulose and / or plant cellulose, and the plant cellulose is cellulose extracted from cotton, straw, discarded bamboo chopsticks and / or wood waste; The metal salt is at least one of chloride, acetate, sulfate and nitrate of iron, cobalt, nickel, copper, zinc, molybdenum, tungsten, indium, tin, bismuth, magnesium, aluminum and calcium.

7. The ion-crosslinked composite cellulose obtained by the preparation method according to any one of claims 1 to 6.

8. A method for preparing an ion-crosslinked composite cellulose separator, characterized in that: The preparation method comprises: adding sodium hydroxide to the preparation method of the ion-crosslinked composite cellulose according to claim 1 for mixing and then filtering to obtain a wet film; soaking the wet film in anhydrous ethanol; and drying the soaked wet film under clamping to obtain an ion-crosslinked composite cellulose membrane.

9. The ion-crosslinked composite cellulose separator obtained by the method for preparing the ion-crosslinked composite cellulose separator according to claim 8.

10. Use of the preparation method according to any one of claims 1 to 6, the ion-crosslinked composite cellulose according to claim 7, the preparation method according to claim 8 and / or the ion-crosslinked composite cellulose separator according to claim 9 in lithium-ion batteries.